Simulation and Determination of the Laws Control of the SRM for the integrated Starter Generator Aplication, ISSN 2278-4209 - Boudouda malik; Naceri Farid (International journal of Electronics Communication and Computer Engineering, 2014)
This paper deals with the design of an integrated starter generator system for a car flywheel based on the Switched Reluctance Machine (SRM) technology. First, we discuss about the starter generator problematic following the results of our bibliography research, and secondly, we briefly remained generalities about the SRM and the determination of the laws control. In addition, we designed the converter associated to the machine using (Matlab/Simulink) software in order to identify the laws control and to adapt to the operating modes (motor, generator, booster, brake). Finally, simulations of the open and closed loop model were performed on the converter with machine (SRM).